Peran SDA dan Teknologi Terhadap Perekonomian Pesisir - Muhammad Yasin; Khosnol Khotimah; Alvazaki Ikbar M (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Indonesia's marine natural resources are one of the efforts to support Indonesia's national development vision to become a maritime axis through the management and utilization of marine natural resources. According to Kartamihardja, et al (2009:3), fisheries potential is of the opinion that Indonesia's public waters have a high diversity of fish species, so that people can take advantage of this fisheries potential. Based on measured data, according to Nuitja (2019:1), Indonesia has 95,181 km of coastline, with approximately 5 million areas of economic exclusion zone. The enormous potential of marine resources needs to be utilized optimally to encourage the maritime sector in Indonesia.